The Impact of The Right to Food on International Trade in The Russia-Ukraine War - Ahmad Yahaya Abdurrahaman; Nilam Andalia Kurniasari (Universitas Airlangga, 2023)
Many discussions about the Right to Food (RTF) and international trade have concluded that international trade has always aided in realizing the RTF. This is reflected in the FAO’s 2004 Right to food Guidelines. It emphasized the importance of international trade in promoting global economic growth and food security, as well as the commitment of states under the WTO Agreement on Agriculture to avoid market restrictions and distortions. The narrative has shifted with the advent of the Russian-Ukraine War. Ukraine and Russia supplied a quarter of the world’s grain before the war. Russia’s blockade of Ukraine’s Black Sea ports has prevented the country from realizing its export potential, contributing to a global food crisis, raising food prices, and putting pressure on global trading systems. Despite sanctions that further restricted international trade, Russia remained defiant until the Black Sea Grain Initiative emerged. This article examined the inter-legal links between the RTF and other fundamental rights, making it indispensable in international trade, humanitarian, and maritime law. The doctrinal legal research method is adopted to analyze the legal position and propositions underlying this topic in the context of the Russia-Ukraine war. The author finds that the state’s duty to respect, protect, and fulfil the RTF is a powerful tool for ensuring international peace and economic order. The work further draws on the Black Sea Grain Initiative to demonstrate that global trade can be preserved and revitalized by promoting the RTF. In conclusion, the article suggests improving and expanding this initiative while submitting that despite being viewed as a partial solution to risks posed by the war, the humanitarian agreement has provided eternal hope of encouraging states to explore diplomatic channels towards future crises, given their commitment to protecting the RTF and freedom from hunger.